The Application of Unmanned Aerial Vehicles (UAV) in Alleviating Time Overrun in the Construction Industry - Thoo, Yuan Leng (2020)
Time overrun has been one of the major issues faced by the construction industry in Malaysia for the recent time being. Construction task has been executed in a slow manner as traditional method is being practiced and human being are being employed carry out those tasks. However, a series of technologies have been invented and being implemented in the construction industry in order to save time required for each construction task. In such a case, one of the newly implemented technology, Unmanned Aerial Vehicles (UAV) will be discuss and identify effect of its implementation towards time overrun issues. The project title for this dissertation is named The Application of Unmanned Aerial Vehicles (UAV) in Alleviating Time Overrun issues in the Construction Industry. The aim of this dissertation is to identify recognize UAV implementation does alleviate delay that lead to time overrun in the construction project. Data is collected from six respondents by using qualitative method as the number of UAV applicants in construction industry is limited. The targeted respondent for the study is G7 contractor who is financially capable to employ such technology in Selangor area. Thus, data collected will be coded and tabulated for data analyzation purposes. Content analysis is being employed to analyze data collected in the dissertation. Hence, the findings are showing the functions of UAV and those functions that can be implemented in the construction industry. In addition, the adoption level of UAV in the construction industry at the current moment is being scrutinize in the study. Although UAV implementation is increasing the efficiency and effectiveness in carrying out construction task, the results reveal the possibility of UAV implementation in lessen time overrun issues is low. The respondents did clarify that UAV is being employed as a tool in the construction industry.